Augmenter of Liver Regeneration Protects Renal Tubular Epithelial Cells From Ischemia-Reperfusion Injury by Promoting PINK1/Parkin-Mediated Mitophagy - Zhu, Dong-Ju; Liao, Xiao-Hui; Huang, Wen-Qi; Sun, Hang; Zhang, Ling; Liu, Qi (Frontiers in Physiology, 2020)
Ischemia-reperfusion(I/R) injury is the most common cause of acute kidney injury (AKI). Accumulating evidence indicates that PINK1/Parkin-mediated mitophagy plays a renoprotective role in the pathogenesis of AKI via reducing ROS production, mitochondrial damage, and the inflammatory response. Augmenter of liver regeneration (ALR), originally identified as hepatic stimulator factor, is a widely distributed multi-functional cytokine in living cells. Our previous study showed that ALR alleviates tubular epithelial cells apoptosis and promotes renal function in rats with AKI. However, the specific mechanism has yet to be elucidated. Because ALR is Our results confirmed that mitophagy has protective effects in I/R injury and ALR alleviated HK-2 cell injury by promoting PINK1/Parkin-mediated mitophagy.Moreover, ALR may be a regulator of the PINK1/Parkin pathway. Consequently, ALR may serve as a new therapeutic target for AKI in the future.